Sustainable Real Estate and Resilient Cities Management, Assessment and Innovations - De Paola, Pierfrancesco; Tajani, Francesco; Locurcio, Marco; Di Liddo, Felicia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Production and consumption activities have determined a weakness in the sustainable real estate economy. The main problems are the subordination of public decision-making, which is subjected to pressure from big companies; inefficient appraisal procedures; excessive use of financial leverage in investment projects; the atypical nature of markets; income positions in urban transformations; and the financialization of real estate markets with widespread negative effects. Furthermore, the overestimation of demographic growth has highlighted the need for urban planning processes to be restructured by limiting an area's building potential, mitigating the loss of place identity with high environmental and cultural value, and preventing uncontrolled land use, as well as through the valorisation and recovery of the area's existing heritage. In this context, economic, social, and environmental demands are combined with uncertainties related to the COVID-19 pandemic. This Special Issue book deals the most recent real estate evaluation methodologies, econometric models, sustainable building management, building costs, risk management and real estate appraisal, mass appraisal methods applied to real estate properties, urban and land economics, transport economics, the application of economics and financial techniques to real estate markets, the economic valuation of real estate investment projects, the economic effects of building transformations or projects on the environment and sustainable real estate, the analysis of the effects of COVID-19 on real estate markets dynamics, and the hit on the resilient cities' development processes.